2016
DOI: 10.1080/02763869.2016.1189782
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Service Desk Quality at an Academic Health Sciences Library

Abstract: ABSTRACT. Due to an identified need for formal assessment, a small team of librarians designed and administered a survey to gauge the quality of customer service at their academic health sciences library. Though results did not drive major changes to services, several important improvements were implemented and a process was established to serve as a foundation for future use. This paper details the assessment process used, as well as lessons learned during the project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In order to address this gap, libraries have since examined a variety of aspects of service in order to demonstrate value and efficiency, from quality of service desk service, to satisfaction with a rapid search service and clinical library financial impact, to a variety of other methods (116)(117)(118)(119)(120)(121)(122)(123).…”
Section: Fig 3 Spectrum Of Servicesmentioning
confidence: 99%
“…In order to address this gap, libraries have since examined a variety of aspects of service in order to demonstrate value and efficiency, from quality of service desk service, to satisfaction with a rapid search service and clinical library financial impact, to a variety of other methods (116)(117)(118)(119)(120)(121)(122)(123).…”
Section: Fig 3 Spectrum Of Servicesmentioning
confidence: 99%
“…Face validity was the most common type of validity represented, as nine authors (31%) had pre-tested their instruments; however, we found that in two cases (7%) (Akor & Alhassan, 2015;Blevins, DeBerg, & Kiscaden, 2016) only librarian colleagues participated rather than members of the target population or instrument development specialists. The pre-testing process with potential respondents varied; Blake et al (2016) held campus interview sessions, while Butler and Byrd (2016) informally polled library student employees.…”
Section: Face Validitymentioning
confidence: 83%
“…" Yan, et al (2015) were not clear, as it seemed they gave their scale two midpoint labels, "Neutral" and "Not Familiar." Most 5-point scales had a midpoint labeled "Neutral" (Askew, 2015;Blevins, et al, 2016;Boyce, 2015;Huang et al, 2015;Mohindra & Kumar, 2015) or "Neither Agree nor Disagree" (Jacoby et al, 2016;Masrek & Gaskin, 2016). Three authors did not report the label used for their midpoint (Chen, 2016;Ganaie, 2016;Swoger & Hoffman, 2015).…”
Section: Q1: How Did Lis Researchers Gather Data On Patron Satisfactimentioning
confidence: 99%
See 1 more Smart Citation